Component composition of flavonoid pigments and flower color in Prunus mira and hybrid cultivars of ornamental peach - L. D. Komar-Tyomnaya; G. P. Zaitsev (Труды по прикладной ботанике, генетике и селекции)
Background. Ornamental peaches are flowering trees with petals ranging in color from white and pale pink to purplered. Because peach suffers from fungal infections, Prunus mira Koehne is often used in breeding programs as a donor of resistance. It also impacts on other traits, including flower color. The aim of this work was to study the composition of flavonoid pigments in the flowers of parent plants and new ornamental peach cultivars originated from P. mira.Objects and methods. Four new cultivars developed at the Nikita Botanical Gardens and their parental forms – P. mira and 4 cultivars with the P. persica morphotype – were included in the study. Pigments were extracted with acidified ethyl alcohol from fresh petals and identified by HPLC analysis.Results. Twelve glycosides of cyanidin and peonidin in different combinations and 8 glycosides of kaempferol and quercetin were found in the petal samples. Among colored plants, the highest amount of flavonols (114 mg g-1) and the lowest amount of anthocyanins (0.46 mg g-1) were found in P. mira petals. Anthocyanins predominate in cultivars with purple-red petals (16 mg g-1). Much more flavonols (55–88 mg g-1) and little anthocyanins (1.2–3.4 mg g-1) were accumulated in the purple-pink flowers of hybrid cultivars. This trend persisted in the cultivars from crosses with a white-flowered parent. Conclusion. The ratio of anthocyanins and flavonols in the peach flowers depends on the plant species and determines the petals’ intermediate colors and half-tones. Using P. mira in breeding programs provides opportunities for the development of cultivars with new shades of flower color.